An interesting case of a wristwatch associated open wrist fracture - Saiyed, Abrar Ali; Darr, Mohammed Qasim; Ghulam, Sahdia (International Journal of Research in Medical Sciences, 2024)
Wrist fractures are commonly encountered injuries during bicycle accidents. Wrist fractures represent the most prevalent upper extremity fractures and account for over a sixth of all fractures seen in emergency department visits. Despite their common occurrence, many cyclists wear wristwatches without considering the potential consequences this may have during an accident when they sustain an upper limb injury. We present a unique case involving a 59-year-old woman with a wristwatch-associated open distal radio-ulnar fracture sustained from a cycling road traffic accident with the crown of the wristwatch being found embedded in the ulna shaft. Currently, there exists a limited knowledge in the literature addressing the safety implications of wearing wristwatches while cycling. This case serves to highlight the hazards associated with wristwatch use during cycling and underscores the hypothesis that wristwatches may act as stress risers, potentially exacerbating fracture severity and necessitating more intricate surgical interventions and subsequent follow-up care.